Double-stapled anastomosis without “dog-ears” reduces the anastomotic leakage in laparoscopic anterior resection of rectal cancer: A prospective, randomized, controlled study - Yang, Yuanfeng; Ding, Feng; Xu, Tianbao; Pan, Zhen; Zhuang, Jinfu; Liu, Xing; Guan, Guoxian (Frontiers in Surgery, 2023)
Background. Anastomotic leakage (AL) is a major cause of postoperative morbidity and mortality in the treatment of colorectal cancer. The aim of this study was to investigate whether the resection of "dog-ears" in laparoscopic anterior resection of rectal cancer (called modified double-stapling technique, MDST) could reduce the rate of AL in patients with middle and high rectal cancer, as compared with the conventional double-stapling technique (DST). Methods. The clinical data of 232 patients with middle and high rectal cancer were prospectively collected from September 2015 to October 2018. They were randomly divided into the MDST group (n=116) and the DST group (n=116) and the data were prospectively analyzed. Morbidity and AL rate were compared between the two groups. Results. Patient demographics, tumor size, and time of first flatus were similar between the two groups. No difference was observed in the operation time between the two groups. The AL rate was significantly lower in the MDST group than in the DST group (3.4 vs 11.2%, p=0.032). The age and anastomotic technique were the factors associated with AL according to the multivariate analysis. The location of the AL in the DST group was further investigated, revealing that AL was in the same place as the “dog-ears” (11/13, 84.6%). Conclusions. Our prospective comparative study demonstrated that MDST have a better short-term outcome in reducing AL compared with DST. Therefore, this technique could be an alternative approach to maximize the benefit of laparoscopic anterior resection on patients with middle and high rectal cancer. The “dog-ears create stapled corners potentially ischemic, since they represent the area with high incidence of AL.